Monitoring for metalaxyl resistance in populations of Phytophthora infestans and their characteristics in Punjab - C. MOHAN; JOGINDER PAUL, T.S. THIND, LAKHVIR SINGH (Indian Phytopathology, 2002)
Base-line study of three sensitive populations of Phytophthora infestans showed mean MIC value as 7.0 /lgl ml for metalaxyl. Out of 68 populations of P. infestans, collected during 1996-99 from different potato fields in Punjab and from two potato areas in U.P. treated with fungicides including Ridomil MZ, majority exhibited normal sensitive response to metalaxyl. Thirty one populations, mostly from Hoshiarpur district, showed mild to severe infection at 10 /lglml, while 12 populations collected mostly during 1998-99 showed varying levels of infection at 50 /lglml. When tested at higher concentrations, three populations were able to produce symptoms at 100 and 200 /lglml thus showing resistant response to metaiaxyl. The resistance factors of the low to moderately resistant populations ranged between 2.85 to 28.57. However, most of these populations were well checked by Ridomil-MZ at the recommended dose of 0.2 % except P-46 which could cause infection at this concentration. Three sensitive populations of P. infestans were able to acquire resistance to 100, 200 and 500 /lgl ml of metalaxyl, respectively under laboratory conditions. The resistant populations were highly pathogenic and no cross resistance was observed to any of the fungicides tested except ofurace.